„Czyż i Afryka nie jest pełna ciał świętych męczenników?” (Augustyn, Ep. 78, 3). Męczeństwo jako rys duchowości Afryki Północnej. - Wysocki, Marcin (Vox Patrum, 2019)
Certainly one of the greatest phenomena of Christianity are the masses of martyrs who gave and still give their lives for Christ. In particular, martyrdom’s spirituality was characteristic of the first centuries of Christianity, and Roman Africa was undoubtedly the region that exceled in the number of martyrs, in the number of known acts of martyrdom and encouragements for martyrdom. In this article, based on existing ancient testimonies from the writings of Tertullian, Cyprian, the acts of the martyrs, Augustine, Arnobius and Lactantius, martyrdom is shown as one of the main features of North African spirituality.